An Experience Sampling Study of PTSD and Alcohol Related Problems - Gaher, Raluca M. (Psychol Addict Behav, 2014)
Posttraumatic stress disorder (PTSD) represents a debilitating psychiatric condition that is affecting the lives of many returning veterans. PTSD and alcohol use and dependence are highly comorbid. The purpose of this study was to understand the functional mechanisms between PTSD and alcohol use and problems. Specifically, the role of negative urgency and emotional intelligence were investigated as vulnerability and resiliency factors, respectively. This study utilized experience sampling to test associations between PTSD symptoms and alcohol use and related problems in a sample of 90 OIF/OEF veterans. Participants completed eight brief questionnaires daily for two weeks on palmtop computers. Elevations in PTSD symptoms during the day were associated with subsequent increases in alcohol use and associated problems that night. PTSD symptoms were associated with greater problems above and beyond the effect of drinking level at both the within- and between- person level. Emotional intelligence was associated with lower negative urgency, fewer PTSD symptoms, and less alcohol use and associated problems. The effects of emotional intelligence were primarily indirect via negative urgency and the effects of negative urgency on alcohol use and problems were indirect via its positive association with PTSD symptoms. Hypothesized cross-level effects of emotional intelligence and negative urgency were not supported. The findings suggest a functional association between PTSD symptoms and alcohol consumption. The association between PTSD symptoms and alcohol consumption is consistent with a self-medication model. However, the significant associations between PTSD symptoms and alcohol problems, after controlling for use level, suggest a broader role of dysregulation.